PENGARUH DANA ALOKASI UMUM, PENDAPATAN ASLI DAERAH, SISA LEBIH PEMBIAYAAN ANGGARAN DAN LUAS WILAYAH TERHADAP BELANJA MODAL (Studi Empiris Pada Pemerintah Kabupaten/Kota di Provinsi Riau) - Ginting, Rahmi; Rasuli, M; Diyanto, Volta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this research is to know and explain about (1) Effect of general allocation funds, (2) local revenue, (3) residual over budgetery financing and (4) area of expenditure to capital expenditure at district/municipal governments in riau province. The population of this research is city governments in Riau Province in 201-2015. This study uses secondary data in the form of realization report of revenues and expenditures of district/municipality governments in Riau Province in 2011-2015 and data on the area obtained from the central statistical agency of Riau Province. Hypothesis testing in this study using multiple linear regression with t test, f test, and test coefficient of determination. The results of this study indicate that the general allocation funds, local revenues and the size of the region affect the capital expenditure. While the residual over budgetary financing has no effect on capital expenditure.Keywords : General Allocation Funds, Local Revenues, SiLPA, Area of Expenditure, Capital Expenditur